Effect of raising cycles on mechanical, comfort, and hand properties of artificial suede. Issue 18 (November 2014) - Roh, Eui Kyung; Oh, Kyung Wha; Kim, Seong Hun
This study evaluated the effect of the raising condition on the mechanical, comfort, and hand properties of artificial suede made ofnylon/polyester microfibers, and identified those best suited for the consumer's needs. The suede became thicker and heavier; in addition, the wale density increased by repeated raisings as the base knits contracted and naps increased after a repeated raising process. Water vapor transmission decreased, but thermal resistance and water repellency increased. The increased number of raisings caused the suede to stiffen and not readily deform by compression; however, the suede had a soft and smooth surface. The thickness, weight, wale density, thermal resistance, and perception of luxuriousness increased between one and four cycles and remained unchanged at six cycles. The hand preference, preference for jackets, and luxuriousness of the suede improved with the number of raisings, with the best performance obtained at four raising cycles.